Distinct temporal filtering mechanisms are engaged during dynamic increases and decreases of noxious stimulus intensity. Issue 10 (October 2015) - Mørch, Carsten Dahl; Frahm, Ken Steffen; Coghill, Robert C.; Arendt-Nielsen, Lars; Andersen, Ole Kæseler
Abstract : Abstract: Physical stimuli are subject to pronounced temporal filtering during afferent processing such that changes occurring at certain rates are amplified and others are diminished. Temporal filtering of nociceptive information remains poorly understood. However, the phenomenon of offset analgesia, where a disproportional drop in perceived pain intensity is caused by a slight drop in noxious heat stimulation, indicates potent temporal filtering in the pain pathways. To develop a better understanding of how dynamic changes in a physical stimulus are constructed into an experience of pain, a transfer function between the skin temperature and the perceived pain intensity was modeled. Ten seconds of temperature-controlled near-infrared (970 nm) laser stimulations above the pain threshold with a 1°C increment, decrement, or constant temperature were applied to the dorsum of the hand of healthy human volunteers. The skin temperature was assessed by an infrared camera. Offset analgesia was evoked by laser heat stimulation. The estimated transfer functions showed shorter latencies when the temperature was increased by 1°C (0.53 seconds [0.52-0.54 seconds]) than when decreased by 1°C (1.15 seconds [1.12-1.18 seconds]) and smaller gains (increase: 0.89 [0.82-0.97]; decrease: 2.61 [1.91-3.31]). The maximal gain was observed at rates around 0.06 Hz. These results show that temperature changes occurring around 0.06 Hz are best perceived and that a temperature decrease is associated with a larger but slower change in pain perception than a comparable temperature increase. These psychophysical findings confirm the existence of differential mechanisms involved in temporal filtering of dynamic increases and decreases in noxious stimulus intensity. Abstract : Offset analgesia could be activated with a feedback-controlled near-infrared laser system. Larger and delayed response to temperature decrease than to temperature increase was observed.